P11.59 Integrin a5 heterogeneous expression in glioblastoma is related to glioma stem cell subpopulations. (6th September 2019) - Dontenwill, M; Mercier, M; Gillmann, G; Reita, D; Lelong-Rebel, I; Noulet, F; Idbaih, A; Herold-Mende, C; Bagnard, D; Spenlé, C; Martin, S
Abstract: BACKGROUND: Glioblastoma (GBM) is the most aggressive primary brain tumor. Treatment failure and recurrence are explained in part by tumoral heterogeneity. Our previous results showed that the integrin α5β1 is implicated in GBM aggressiveness and represents a relevant therapeutic target. Recently, we observed intra- and inter-tumor heterogeneity of integrin α5β1 expression. Heterogeneity may be linked to different glioma stem cell populations. MATERIAL AND METHODS: Ten glioma stem cell lines were grown as neurospheres in stem cell medium and their differentiation was induced by serum and/or ATRA. Two cell lines (NCH421k and NCH644) were selected and were modified by depletion (CrisprCas9) or transfection of the α5 integrin gene. Polyclonal lines and individual clones were analyzed phenotypically in vitro, before and after differentiation, and in vivo in orthotopic xenografts of 2x10 4 cells in nude mice. TCGA datasets were used to validate the heterogeneous expression of α5 integrin in GBM. RESULTS: TCGA data validate that α5 integrin mRNA was only over-expressed in the mesenchymal subclass of GBM. Our results show that α5 integrin protein is not expressed in stem cell culture conditions. However, α5 integrin expression is induced after differentiation in only half of the cell lines supporting the notion of tumoral heterogeneity of glioma stem cells. Interestingly, single cell-derived clone evaluation showed that intra-tumoral stem cell heterogeneity also exists at the level of α5 protein expression. When glioma stem cells are programmed or transduced to express α5 integrin, differentiated cells became more aggressive. Notably, they acquired a fibronectin-dependent motility and a proliferative phenotype. Interestingly, integrin α5 remained expressed in secondary stem cells obtained after dedifferentiation. The in vivo assays suggested that glioma stem cells, programmed to express the integrin, were prone to form larger tumors. CONCLUSION: Our data support the hypothesis that some glioma stem cells are programmed to express the α5 integrin subunit in their differentiated progeny to form a more aggressive tumor. They add new evidences that both cell populations may be considered for new therapeutic strategies against GBM.